Penggunaan Ampas Bir dalam Ransum untuk Meningkatkan Kualitas Daging Domba - Agus Priyono; S.N.O. Suwandyastuti; Ning Iriyanti (Jurnal Agripet, 2013)
The utilization of brewery waste in ration to improved the quality of lamb meatABSTRACT. An experiment has been conducted to study the utilization of brewery waste in ration to improved the meat quality of lamb. High quality of lamb meat can be reached by manipulation of rumen fermentation. Tannins in brewery waste can decrease the activity of rumen microorganism and inhibite the rumen biohydrogenation processes. The experiment was conducted with an experimental method by in vivo technique, using 16 heads of local lamb, 4-5 months old, with body weight range of 5-10 kg. The trial was conducted for 150 days, using Completely Randomized Block Design with 4 replicates. The treatment tested were 4 levels of Brewery Waste : R1 = 12%; R2 = 24%; R3 = 36% and R4 = 48%. The variables measured were : physical and chemical quality of meat. The result indicated, that the treatment tested significantly affect the meat quality physically, except to the percentage of edible distal meat and proximal bone weight.Based on the all variables measured, the research conclusion : (1) the utilization of brewery waste up to 48% dry matter ration, could be used, without any physiology and metabolism disturbance; (2) the highest increasing of unsaturated fatty acid was stearic acid (C18:0) as much as 54. 60%, was reach by R3 (36% brewery waste); the linoleic acid increased as much as 43.91% reach by R4 (48% brewery waste); the oleic acid increased as much as 37.48% by R2 ( 24% brewery waste). From the result can be suggested that the need of tannin brewery waste as biohydrogenation inhibitor would be more effective and efficient whenever brewery waste usage has been increased up to 60% dry matter ration.